Rural secondary school children’s positioning on children’s human rights: a case study of Gonawapotera Secondary School. - Tshuma, Future (Midlands State University, 2017)
This study sought to investigate rural secondary school children’s positioning on children’s human rights: a case study of Gonawapotera Secondary School. Questionnaires and interviews were used as data collecting instruments in the process of gathering data. Eight teachers at Gonawapotera Secondary School, thirty pupils and twenty parents were randomly selected as participants for the study. Data was then presented and analysed thematically. The major findings showed that children’s rights are causing more problems than benefits in rural secondary schools as evidenced by lack of discipline and poor pass rate. The researcher however found out that the major problem is on lack of knowledge on children’s rights as witnessed by pupils, parents and teachers themselves. The researcher therefore recommends that in-service training should be done to educate teachers. Workshops should be carried out for parents to be aware of children’s rights and human rights education should be included in the curriculum to address the problems at hand.